"Manguni," A Minahasan Cultural Identity: The Application of Practice-Based Research on A Program Music - Gosal, Clifford Israel; Listya, Agastya Rama; Komalig, Yudi Novrian; Tan, Arwin Quiñones (Resital: Jurnal Seni Pertunjukan, 2024)
Manguni is a Minahasan term for a carnivorous, nocturnal bird known as an owl. The manguni has the Latin name otus manadensis. Minahasan people believe that the manguni is a bird that brings news from Opo Wailan Wangko or God Almighty. In the modern era, mangunis have become endangered due to hunting and logging of trees that were mangunis' original habitat. The extinction of these birds has impacted the younger generation's understanding of the manguni as the identity of the Minahasan people, as well as the ancestral cultural values found in this bird. This research aims to introduce and preserve the noble values found in manguni to the younger generation through symphonic works that combine Minahasan and Western musical idioms. The use of orchestral instruments in nationalistic works has also been done by Romantic-era composers such as Bedrich Smetana, Antonin Dvorak, Bela Bartok, Zoltan Kodaly, and others. However, Manguni is the first orchestral composition to capture the magical figure of this bird musically. This research applies a qualitative and practice-based approach that positions the researcher as the vital instrument. Several stages of research include conceptualizing the composition, incorporating leitmotifs, adding extramusical ideas, pouring ideas or creations, composing detailed compositions, and evaluating. The research output is a descriptive programmatic musical work that uses manguni as an extramusical idea. Leitmotifs represent the nature and character of the manguni and its meanings to the Minahasan people. The work adopts Minahasan musical idioms, such as the rhythmic patterns of Kabasaran dance and the modes and ornamentation of Maengket singing. The Manguni movement is written in a sonata form consisting of exposition, development, recapitulation, and coda. The techniques used include polytonal, cluster, quartal, artificial harmony, polychord, sequence, augmentation, diminution, and retrograde.